A COMPETITIVIDADE E O GRAU DE CONCENTRAÇÃO DAS EXPORTAÇÕES DO COMPLEXO SOJA DO BRASIL, DA ARGENTINA E DOS ESTADOS UNIDOS DA AMÉRICA NO PERÍODO 1995/2010 - Freitas, Guilherme da Silva; Massuquetti, Angélica (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper analyzes the export competitiveness of soybean in Brazil, Argentina and the United States and the degree of concentration in the main export markets of these countries in the period 1995/2010, using both the index of Revealed Comparative Advantage (RCA) and Concentration ratio (CR). The results reveal, based on the CR3 , that Argentina and Brazil show an increase in the concentration ratio of even crushed soybeans and crude soybean oil, while the US in even crushed soybeans and fractionated soybean oil even. The RCA index shows advantages for all products/countries in both years, except the soy flour to Brazil and Argentina that had values below one. For the US the indexes were lower when compared to the other countries, although it remained as the main exporter of soy flour, fractionated soybean oil even and even crushed soybeans.